Children, Curfews, and the Constitution - Katherine Hunt Federle (Washington University Law Quarterly, 1995)
In this Article, I propose an account that redresses the powerlessness of children. Any such account must approach the problem of children's rights by rejecting capacity as an organizing principle. Furthermore, this approach acknowledges that rights have value because they have empowering effects which reduce victimization and marginalization and permit challenges to hierarchy and inequality. This approach takes power as a central principle and contends that in any given dynamic, power is the organizing force. From this perspective, a right, in its most fundamental sense, is power accorded to the least powerful party in any given dynamic.
Keywords: Youth curfews